CircDHRS3 inhibits prostate cancer cell proliferation and metastasis through the circDHRS3/miR-421/MEIS2 axis - Dai, Xiyu; Chen, Xinan; Chen, Wensun; Ou, Yuxi; Chen, Yiling; Wu, Siqi; Zhou, Quan; Yang, Chen; Zhang, Limin; Jiang, Haowen (Epigenetics, 2023)
Prostate cancer is the most prevalent type of cancer among men worldwide. The importance of circular RNA (circRNA) in prostate cancer and its connection to malignancy has been steadily recognized. circRNA expression was obtained by circRNA sequencing of prostate cancer. circRNA and its function were further analysed. The results were verified by qRT-PCR, RIP assay, FISH, RNA pulldown, WB, CCK-8, colony formation assay and wound-healing assay. BALB/c Nude mice were used for xenograft hosts. Low expression of circDHRS3 was assessed in prostate cancer. Overexpression of circDHRS3 inhibited prostate cancer growth and migration in vitro. Additionally, miR-421 was shown to be the downstream target of circDHRS3, as shown by fluorescence in situ hybridization and dual-luciferase experiments. The rescue assay results for the PC3 and Du145 cell lines demonstrated that circDHRS3 inhibits prostate cancer cell lines' ability to proliferate and metastasize by modulating MEIS2 expression through the circDHRS3/miR-421/MEIS2 axis. In vivo investigations confirmed that the overexpression of circDHRS3 could inhibit both the lung and bone metastasis of prostate cancer cells. circDHRS3 has the potential to become a biomarker and a targeted therapeutic site for prostate cancer, particularly in the malignant stage. Our study indicates that circDHRS3 inhibits prostate cancer cell proliferation and metastasis through the circDHRS3/miR-421/MEIS2 axis.